Effects of Melatonin on Some Antioxidant Enzymes in Streptozotocin-induced Diabetic Rats - Ercan Keskin; Durmuş Hatipoğlu; Deniz Uluışık (Türk Spor ve Egzersiz Dergisi)
In this study, it was aimed to determine the effects of melatonin application in experimentally induced diabetes. For this purpose, thirty two adult male Wistar Albino rats were used. Animals in control group were not any treatment. Melatonin group animals received 50 mg/kg melatonin intraperitoneally in daily for eight weeks. Diabetes was induced by subcutaneous injections of streptozotocin at dose of 40 mg/kg for two days as a single dose per day in diabetes group animals. Animals in Diabetes+Melatonin group were made diabetic by streptozotocin in the same way and then these animals received 50 mg/kg melatonin intraperitoneally in daily for eight weeks. In blood samples taken from all animals, insulin, glucose, HbA1c, MDA, GSH, SOD were determined. The insulin level in diabetes group was lower than control group, while blood glucose level was higher (p lt;0.05). Melatonin treatment to diabetic animals resulted in significantly differences in these parameters compared to diabetes group (p lt;0.05). HbA1c in diabetes group was higher than control group (p lt;0.05). Melatonin application to diabetic animals significantly decreased HbA1c compared to diabetes group (p lt;0.05). In diabetes group, GSH and SOD levels were found to be lower than control group, whereas MDA level were high (p lt;0.05). The changes in GSH and SOD levels with melatonin application to diabetic animals were not important compared to diabetes group, while MDA level was significantly reduced (p lt;0.05). As a result, we concluded that the melatonin treatment to experimentally induced diabetic rats obviously improved the some negative changes in metabolic parameters resulting from diabetes.